Remote Sensing in the Analysis of the Ponds Alignment in the Nhecolandia Pantanal, MS - Oliveira, Ana Paula Garcia; Mioto, Camila Leonardo; Ribeiro, Alisson André; Jaquez, Robson; Albrez, Edilce do Amaral; Sígolo, Joel Barbujiani; Assine, Mario Luis; Paranhos Filho, Antonio Conceição (Anuário do Instituto de Geociências, 2016)
Among the several kinds of pantanais, the Nhecolândia sub-region deserves prominent role for presenting peculiar landscape. Its main feature is the presence of numerous lakes, which are divided into “baías” and “salinas” (fresh and brackish, respectively). The study aimed to quantify and analyze the orientation and aligning intensity of the major axes of these water ponds, in order to contribute for understanding the formation and functioning of this intriguing and yet unknown region. Firstly, we adopted the object-oriented classification method on Landsat 5 satellite image, TM sensor. Then, we used a specific algorithm for identifying the alignment of the ponds. As results, we recognized 17,631 lakes, 17,050 being baías and 577 salinas. These ponds are aligned in two directions - NE and NW -, which would be associated to the directions of the winds prevailing during the origin of the Nhecolândia lakes.